A Comparative Study Between Extrovert and Introvert Student’s Achievement in English Conversation Course - Rieke Ayu Oktriani; Indah Damayanti; Mei Hardiah (Universitas Bengkulu, 2021)
This research aimed to find out whether there is a significant difference in achievement between extrovert and introvert students in speaking ability in the English Conversation subject for 2nd-semester students of the University of Bengkulu. This research was causal-comparative research. The subject of this research was students at the 2nd semester English Department Study Program of University Bengkulu who has taken the English conversation subject in the academic year 2019/2020. The researcher used a Questionnaire and achievement result as the instrument. The result of this research shows that there were no significant differences between introvert and extrovert personalitiesin English Conversation Class achievement. It was concluded that the student's personality does not affect the score achieved in the speaking class.